Implementation of the Format for the Nursing Problem Oriented Record (Por) Performance in Investment Health Center in Ternate City 2018 - ., Amira; ., Muhlisa; Johan, Tri (KnE Life Sciences, 2019)
Completeness of nursing documentation is one of the quality indicators of nursing care. Based on the nursing practice law no. 38 article 37, nurses in carrying out Nursing Practices are obliged to document Nursing Care in accordance with the standards. Documentation in Inpatient PKM consisting of Siko, Jambula, and Sulamadaha PKM itself, based on the observations of researchers found several obstacles, namely, the lack of nurses given the large number of PKM programs that must be run, varying levels of education so documentation has a different understanding, this also supported by the lack of education and training related to temporary nursing care documentation relating to the Nursing Process and Documentation experiencing some recent changes. The purpose of this study was to determine the effect of applying the nursing documentation format for the model Problem-Oriented Record (POR) on the performance of nurses in the Inpatient Health Center in Ternate City. The design of this study is quasi-experimental, namely, pre and post-test without control group. The population is nurses with 41 people in PKM Inpatient who are in Ternate City. Samples were taken by total sampling technique and analyzed using statistical tests t-test, Anova, and correlation. The results of the study found a significant difference between the performance of nurses before and after the application of the documentation format for nursing care in the POR model (p-value: 0,0005 α: 0.05) while the characteristics of respondents included age, sex, marital status, length of work and education had no effect on performance.